Prescribed Fire Use Among Black Landowners in the Red Hills Region, USA - Perkins, La’ Portia J.; Coates, T. Adam; Hiers, J. Kevin; Fowler, Cynthia T.; Bigelow, Seth W. (Ethnobiology Letters, 2023)
The Red Hills Region of southern Alabama, northern Florida, and southwestern Georgia is one of the most prominent areas in the United States for conducting prescribed fire research and is the birthplace of fire ecology. The culture of prescribed burning in the Red Hills has been influenced by multiple ethnic groups, including the Seminole and Creek nations, Black landowners, and White researchers. Given the distinctive reliance of the region on prescribed fire, it is noteworthy that the combined issues of Black land loss, underrepresentation, and incentives for using prescribed fire on private lands in the southeastern United States have generated questions about diversity and inclusion in landowner outreach. To increase understanding about Black landowner historic and current use of prescribed fire for land management in the Red Hills Region, formal and informal interviews were conducted from May through August 2019 with 21 Black landowners and tenants to document the perspectives and thoughts of Black landowners and tenants of southern Alabama, northern Florida, and southwestern Georgia. The results of this research show that Black landowners, tenants, and fire experts, have been, and continue to be, influential in the development and sustainment of fire traditions in the Red Hills and in the resilience of the longleaf pine ecosystem.